Empowering Women Digitally: A Randomised Controlled Trial on Digital Financial Literacy and Women's Economic Empowerment in Rural Pakistan - Zubaria Andlib (Global Labor Organization (GLO), 2025)
This study examines the effectiveness of a digital financial literacy intervention aimed at improving financial knowledge, confidence, and behaviour among rural women in Pakistan. Using a randomized controlled trial conducted in two selected villages in the Rawalpindi district, women were assigned to receive digital financial literacy training either individually or jointly with a male household member. The intervention, delivered in person and via mobile phones, focused on core topics including budgeting, saving, and secure digital transactions. The training substantially improved women's financial knowledge, digital confidence, and self-efficacy. The intervention also increased the use of mobile wallets, greater engagement with formal savings mechanisms, and encouraged more consistent budgeting practices. When male household members participated alongside women, the intervention further enhanced women's financial autonomy and promoted more active joint decision-making over household finances. These findings demonstrate the potential of contextually grounded digital interventions to expand women's financial inclusion and highlight the value of household engagement in reinforcing women's economic agency.
Keywords: C93; D14; O16; J16; 330; Digital Financial Literacy; Financial Inclusion; Women's Empowerment; Behavioral Interventions; Randomized Controlled Trial